The Effect of Work Environment and Learning Management on Teacher Performance Mediated by Teaching Activities - Agoes Windarto; Nazaruddin Malik; Achmad Mohyi (University of Muhammadiyah Malang, 2022)
This study attempts to see how much the work environment, learning management, and teaching activities influence teacher performance in SMK Telkom Malang. Using a descriptive correlational research design method, in which the goal of the study is to characterize the existing variables before looking for relationships between them. The total respondent of this research was 75 teachers and academic support personnel, it is clear that the work environment and learning management have a significant impact on teacher performance. The efficiency of teaching activities, on the other hand, mediates the work environment and learning management and has a major impact on teacher performance.